2012
DOI: 10.1002/14651858.cd004118.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Rectal 5-aminosalicylic acid for maintenance of remission in ulcerative colitis

Abstract: The limited data available suggest that rectal 5-ASA is effective and safe for maintenance of remission of mild to moderately active distal UC. Well designed randomized trials are needed to establish the optimal dosing regimen for rectal 5-ASA, to compare rectal 5-ASA with rectal corticosteroids and to identify subgroups of patients who are more or less responsive to specific rectal 5-ASA regimens. The combination of oral and rectal 5-ASA appears to be more effective than either oral or rectal monotherapy for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 23 publications
0
22
0
Order By: Relevance
“…When the disease is limited to left-sided colon, topical therapy with enemas and/or suppositories is very effective in inducing remission in upward of 90% of cases and highly effective at maintaining remission. [47][48][49] However, many patients prefer oral 5-ASA over the topical formulations for ease of administration. In patients with more extensive disease, oral 5-ASAs are used for induction and maintenance of remission.…”
Section: -Aminosalycilatesmentioning
confidence: 99%
“…When the disease is limited to left-sided colon, topical therapy with enemas and/or suppositories is very effective in inducing remission in upward of 90% of cases and highly effective at maintaining remission. [47][48][49] However, many patients prefer oral 5-ASA over the topical formulations for ease of administration. In patients with more extensive disease, oral 5-ASAs are used for induction and maintenance of remission.…”
Section: -Aminosalycilatesmentioning
confidence: 99%
“…11,25,26 By contrast, there is strong evidence to support oral 5-ASAs for the induction and maintenance of remission in ulcerative colitis. [27][28][29] Similarly, topical 5-ASA therapy has a proven efficacy in the induction and maintenance of remission in ulcerative colitis, particularly for distal disease, 30,31 or as an adjunct to oral 5-ASA therapy for induction of remission for more extensive disease. 32,33 Topical steroids, once popular for treating distal ulcerative colitis, are now considered second line or adjunctive to topical 5-ASAs in ulcerative colitis.…”
Section: Introductionmentioning
confidence: 99%
“…The results of a recent meta-analysis indicated that rectal 5-ASA was superior to placebo for inducing symptomatic, endoscopic and histological improvement and remission [54]. Rectal 5-ASA was superior to rectal cortico steroids for inducing clinical improvement and remission [54].…”
Section: -Aminosalycilatesmentioning
confidence: 99%
“…The results of a recent meta-analysis indicated that rectal 5-ASA was superior to placebo for inducing symptomatic, endoscopic and histological improvement and remission [54]. Rectal 5-ASA was superior to rectal cortico steroids for inducing clinical improvement and remission [54]. Three randomized controlled trials were conducted to compare the efficacy of intermittent topical 5-ASAs with that of oral 5-ASAs in preventing the relapse of quiescent UC [55][56][57], and two compared rectal combined with oral 5-ASAs [58,59].…”
Section: -Aminosalycilatesmentioning
confidence: 99%